The Relation between Rainfall and Larval Density of Dengue Hemorrhagic Fever with Spatial Modeling - Luthfiyah Maretha; Rahmatillah Razak; Achmad Fickry Faisya (Media Kesehatan Masyarakat Indonesia, 2022)
Dengue Hemorrhagic Fever (DHF) is a disease transmitted by the aedes aegypti mosquito. This study aims to determine the relationship between rainfall and larval density which consist of House Index (HI), Container Index (CI), Breteau Index (BI), and Larval Free Rate (LFR) on the incidence of dengue hemorrhagic fever using GIS modeling. The research method is quantitative with a spatial approach and Univariate and Bivariate analysis. The study population was all cases of DHF in all working areas of Lahat District Health Center, Lahat Regency in 2016-2019. The results of the statistical correlation test showed that there was a correlation between rainfall and the incidence of DHF with a value (p=0.003), while larval density showed a correlation between HI and the DHF incidence (p-value=0.007), CI (p-value=0.007), BI (p-value=0.007). ABJ (p-value=0.012). Spatially, it was found that the incidence of dengue fever was high in the working regions of Public Health Center with high HI (≥5%), low CI (<10%), low BI (<50%), and low larvae-free rate (<95%). It can be concluded that there is a relation among rainfall, HI, CI, and BI on the incidence of DHF in Lahat Regency in 2016-2019 and spatially shows the high incidence of DHF in high HI (≥5%) and low LFR (<95%). It is recommended that the Lahat Regency Office used climate information from the BMKG in planning a program to eradicate DHF and eradicate mosquito nests during the rainy season in Lahat District.